Strengthening Governance of Waqf in the Kingdom of Saudi Arabia: Status, obstacles, and institutional transformation - AlNemer, Hashem (Archives of Business Research, 2022)
Waqf is considered as an important institution in the Islamic world for enhancing socio-economic development and increasingly attracting public interest with respect to accountability and transparency in its governance. Thus, the public has continued to demand greater clarity and best services from the institutions of waqf, especially when it comes from a country like Saudi Arabia, which possesses the most valuable waqf industry in the world. As 74% of the endowments of Waqf entities in Saudi Arabia are unknown with missing information and reports, there are many accusations about the efficiency and inability of the current waqf regulations and standards to control. The Saudi Vision 2030 asserts the importance of Waqf in financing and enhancing the socio-economic projects with a prediction growth plan to reach SR 350B by 2030. This paper explores the existing regulations and standards used by the Saudi Waqf Authority to manage and control local waqf institutions. A qualitative approach has been used to assess the obstacles, investment channels, the emergence of a new awqaf system, and the way forward for the new waqf Authority in Saudi Arabia through appraisal of documents and publications and in-depth interviews of key stakeholders. Based on the findings, several recommendations have been made to adopt the best Waqf practices, regulations, and governance.